A The Meaning Of Ikan Mas Arsik In Batak Toba Culture - Simaremare, Perawati; Marwanti (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2025)
Culture is the wealth of a nation and must always be preserved.